STRUKTUR MAKAM K.H. TUBAGUS LATIFUDDIN PAGERAJI, KABUPATEN MAJALENGKA - Ukun Abdul Syukur (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
Majalengka is an area in Tatar Sunda that has a long history. This area has even been the basis of a number of kingdoms that once existed in the history records of our nation. When Islam began to spread to Parahyangan area from Cirebon direction, some areas did not immediately accept the religion which came from the Arab land. Two of them are Talaga and Rajagaluh which are located exactly in Majalengka Regency now. The situation is certainly raises many questions considering the current regency is inhabited by the majority of Muslims. Of course one of the things that make it curious is about the gait of the spreaders of Islam in the community. One of the spreaders of Islam in Majalengka is K.H. Tubagus Latifuddin residing in Pageraji. From oral tradition it is known that this charismatic figure has a very significant role to increase the number of adherents of Islam in the area. His very special positioning of his grave shows that K.H. Tubagus Latifuddin is not an arbitrary person, because he still has a permanent place in the heart of society even though this character has long died.Keywords: tombs, the spread of Islam, community leaders, Majalengka